(untitled) (Repertorio Científico, 2024)
With a growing world population and a significant reduction in farmland, the efficiency of agriculture is of utmost importance, both in the use of water and in the correct use of chemical fertilizers, especially nitrogenous sources. For this reason, it is that zeolite was evaluated as an improver in the use of water, through the reduction of evapotranspiration and as an efficientizer of nitrogen fertilizers, thus reducing its. The experimental trial required an indicative crop (corn), based on five treatments (TA: 100% Fertilizer, TB: 25% Z + 75% ½ fertilizer, TC: 25% Z + 75% fertilizer, TD: 25% Z + 75% double fertilizer, TE: 100% Z + 100% fertilizer), with 15 repetitions, to be able to evaluate the consumption of water and fresh and dry weights, in addition to chemical analysis of the soil, to measure the remnant of N and foliar chemical analysis To observe the nutrient consumption, the C / N ratio was also evaluated, to show the influence of the mineral on the soil microbiota. The results show that despite the fact that in the first 21 days there is a statistical difference between the treatments, for the other measurements (42 and 70 days) the opposite occurs, a very similar aspect occurs in the development of biomass, where there is no evidence statistical difference. Regarding the presence of remaining N, the treatments with the highest percentage are A and E, presenting these at the same time a greater amount of foliar N, while in terms of the C / N ratio, the highest is presented treatment B (> 10) which, at the same time, has the least amount of fertilizer.